Persepsi Masyarakat tentang Terumbu Karang di Kepulauan Seribu - Mangunsong, Farma (UI Scholars Hub, 2006)
Kepulauan Seribu has rich natural resources in the form of coral reef, coral fish, and other ocean biota which interact with each other. Resident of Kepulauan Seribu has a high dependency on these natural resources. The existence of coral reef has a strong impact on fisheries since the number of fish and other biota will be high when the coral reef is in good condition. Nelayan tangkap konsumsi is one of the job types which strongly affected by the existence of coral reef Fishermen gel economic benefits in the form of job and income source. Not only fishermen, all the residents also get benefits in the form of protein source, income source, and also job field from the existence of coral reef Nevertheless, based on the research done by the experts, the condition of the coral reef in Kepulauan Seribu tends lo get worse because of human and natural factors. The purpose of this study is to reveal the Kepulauan Seribu residence perception of the coral reef condition and factors affect this perception. flased on regression results, place of residency, age, education, length of stay, major souce of hoi:schold income, and condition of coral reef at the nearest island have significant relationships with the people's perception.